Severe adverse events following benzathine penicillin G injection for rheumatic heart disease prophylaxis: cardiac compromise more likely than anaphylaxis. Issue 2 (20th June 2019) - Marantelli, Shannon; Hand, Robert; Carapetis, Jonathan; Beaton, Andrea; Wyber, Rosemary
Abstract : Objective: Secondary prophylaxis through long-term antibiotic administration is essential to prevent the progression of acute rheumatic fever to rheumatic heart disease (RHD). Benzathine penicillin G (BPG) has been shown to be the most efficacious antibiotic for this purpose; however, adverse events associated with BPG administration have been anecdotally reported. This study therefore aimed to collate case reports of adverse events associated with BPG administration for RHD prophylaxis. Study design: A literature review was used to explore reported adverse reactions to BPG and inform development of a case report questionnaire. This questionnaire was circulated through professional networks to solicit retrospective reports of adverse events from treating physicians. Returned surveys were tabulated and thematically analysed. Reactions were assessed using the Brighton Collaboration case definition to identity potential anaphylaxis. Results: We obtained 10 case reports from various locations, with patients ranging in age from early-teens to adults. All patients had clinical or echocardiogram-obtained evidence of valvular disease. The majority of patients (80%) had received BPG prior to the event with no previous adverse reaction. In eight cases, the reaction was fatal; in one case resuscitation was successful and in one case treatment was not required. Only three cases met Level 1 Brighton criteria consistent with anaphylaxis. Conclusion: These results indicate that anaphylaxis is not a major cause of adverse reactions to BPG. An alternative mechanism for sudden death following BPG administration in people with severe RHD is proposed.